1 and 2 Kings ; v. 1 - Jones, Gwilym Henry, 1930- (Grand Rapids, MI Eerdmans, 1984)
Contents : v. 1 : 1 Kings 1 - 16 : 34. Includes bibliographical references and indexes.
Keywords: Bible. O.T. Kings -- commentaries